Factors Affecting Competitive Strategies in International Construction Companies - Ercan, Tugce; Koksal, Almula (YILDIZ TECHNICAL UNIV, FAC ARCHITECTURE, 2013)
Due to rising competition in the international construction market, competitive strategies are becoming ever more important. This study aims to identify the level of importance of a variety of competitive strategies in construction companies to create a theoretical framework for competitive strategies in international construction business. In the questionnaire titled: 'Identifying the Parameters of Strategic Performance Comparison Tool in International Construction Companies', professionals were asked the level of importance of parameters in acquiring a competitive edge in international markets for construction companies. 82 people who currently work for international construction companies responded the questionnaire. The Relative Importance Index (RII) of competitive strategies in construction companies was calculated using the survey results. The construct was redesigned through the Pearson Correlation and principal components analysis (PCA). The results of the PCA denoted that the construct of competitive strategies in construction companies can be explained by three main factors in sync with Porter's three generic competitive strategy types: F1 Cost Leadership in Construction, F2 Specialization and Focus and F3 Differentiation in Construction and Company Resources. The analysis results show that the competitive strategies related to Differentiation in Construction and Company Resources have a greater importance level, while the diversification strategies have a lower importance level. Which means specialization in some type of construction activity and focus on a specific group of customers is more effective than diversification strategies in gaining a competitive advantage in the market.
Keywords: Relative importance index; construction company; competitive strategies; principal component analysis; Architecture